Antibiotic-Resistant Bacteria in Clams-A Study on Mussels in the River Rhine - Nicole Zacharias; Iris Löckener; Sarah M. Essert; Esther Sib; Gabriele Bierbaum; Thomas Kistemann; Christiane Schreiber (MDPI AG, 2021)
Bacterial infections have been treated effectively by antibiotics since the discovery of penicillin in 1928. A worldwide increase in the use of antibiotics led to the emergence of antibiotic resistant strains in almost all bacterial pathogens, which complicates the treatment of infectious diseases. Antibiotic-resistant bacteria play an important role in increasing the risk associated with the usage of surface waters (e.g., irrigation, recreation) and the spread of the resistance genes. Many studies show that important pathogenic antibiotic-resistant bacteria can enter the environment by the discharge of sewage treatment plants and combined sewage overflow events. Mussels have successfully been used as bio-indicators of heavy metals, chemicals and parasites; they may also be efficient bio-indicators for viruses and bacteria. In this study an influence of the discharge of a sewage treatment plant could be shown in regard to the presence of E. coli in higher concentrations in the mussels downstream the treatment plant. Antibiotic-resistant bacteria, resistant against one or two classes of antibiotics and relevance for human health could be detected in the mussels at different sampling sites of the river Rhine. No multidrug-resistant bacteria could be isolated from the mussels, although they were found in samples of the surrounding water body.